Genetic and epigenetic alterations in the GNAS locus and clinical consequences in Pseudohypoparathyroidism: Italian common healthcare pathways adoption. Issue 1 (December 2016) - de Sanctis, L.; Giachero, F.; Mantovani, G.; Weber, G.; Salerno, M.; Baroncelli, G.; Elli, M.; Matarazzo, P.; Wasniewska, M.; Mazzanti, L.; Scirè, G.; Tessaris, D.
Abstract Background Genetic and epigenetic alterations in theGNAS locus are responsible for the Gsα protein dysfunctions causing Pseudohypoparathyroidism (PHP) type Ia/c and Ib, respectively. For these heterogeneous diseases characterized by multiple hormone resistances and Albright's Hereditary Osteodystrophy (AHO) the current classification results inadequate because of the clinical overlap between molecular subtypes and a standard clinical approach is still missing. In the present paper several members of the Study Group Endocrine diseases due to altered function of Gsα protein of the Italian Society of Pediatric Endocrinology and Diabetology (ISPED) have reviewed and updated the clinical-molecular data of the largest case series of (epi)/genetically characterized AHO/PHP patients; they then produced a common healthcare pathway for patients with these disorders. Methods The molecular analysis of theGNAS gene and locus identified the causal alteration in 74 subjects (46 genetic and 28 epigenetic mutations). The clinical data at the diagnosis and their evolution during up to 15 years follow-up were collected using two different cards. Results In patients with genetic mutations the growth impairment worsen during the time, while obesity prevalence decreases; subcutaneous ossifications seem specific for this group. Brachydactyly has been detected in half of the subjects with epigenetic alterations, in which the disease overts later in life, often with symptomatic hypocalcaemia, and also early TSH and GHRH resistances have been recorded. Conclusions A dedicated healthcare pathway addressing all these aspects in a systematic way would improve the clinical management, allowing an earlier recognition of some PHP features, the optimization of their medical treatment and a better clinical-oriented molecular analysis. Furthermore, standardized follow-up data would provide new insight into less known aspects.